Root carbon inputs outweigh litter in shaping grassland soil microbiomes and ecosystem multifunctionality - Jiayin Feng; Linlin Wang; Changchun Zhai; Lin Jiang; Yunfeng Yang; Xiaowei Huang; Jingyi Ru; Jian Song; Limei Zhang; Shiqiang Wan (npj Biofilms and Microbiomes)
Abstract Global change has the potential to alter soil carbon (C) inputs from above- and below-ground sources, with subsequent influences on soil microbial communities and ecological functions. Using data from a 13-year field experiment in a semi-arid grassland, we investigated the effects of litter manipulations and plant removal on soil microbiomes and ecosystem multifunctionality (EMF). Litter addition did not affect soil microbial α-diversity whereas litter removal reduced bacterial and fungal α-diversity due to decreased C substrate supply and soil moisture. By contrast, plant removal led to larger declines in bacterial and fungal α-diversity, lower microbial network stability and complexity. EMF was enhanced by litter addition but largely reduced by plant removal, primarily attributed to the loss of fungal diversity. Our findings underscore the importance of C inputs in shaping soil microbiomes and highlight the dominant role of plant root-derived C inputs in maintaining ecological functions under global change scenarios.